IN-BETWEEN IDENTITIES: A COMPARATIVE ANALYSIS OF CULTURAL AND ETHNIC IDENTITY REPRESENTATIONS ON YOUTUBE VLOGS BY THE SECOND GENERATION OF VIETNAMESE DIASPORAS IN WESTERN COUNTRIES (Proceedings of the World Conference on Media and Mass Communication, 2023)
The advent of the Internet and user-generated content (UGC) platforms such as YouTube has made it possible for users to access to online cultural products and cross-border online conversations. In YouTube video blogs (vlogs), anyone with a web access and basic video production can broadcast themselves as a virtual space for social connections, creative outlets or online journals of the users’ personal lives and experiences. While there is the list of influential diasporic Vietnamese YouTubers, whose videos are favored for the narratives about their in - between identities and cultural lives, little has been studied on how Vietnamese diasporic youth use YouTube vlog to express their cultural identity. By applying textual and discourse analysis to study both the production and reception of vlogs by popular diasporic Vietnamese vloggers, this paper finds that a vlog is both an online space for cultural distinctiveness expression and a conversational hub that these vloggers and their audience discuss their collective identity as diasporic young Vietnamese in Australia, Canada, and the USA. In other words, these vlogs are their antidote to the stereotypical portrayals of being a minority in multicultural, yet Western-dominant societies. The study also discovers the repetitively lack of seriousness in these vlogs when discussing issues of their cultural identity to cope with YouTube’s priority to provide entertainment and playful atmosphere. Implications from these findings will help to shed lights on the intersection between diasporicyouths’ agency of producing their own ethnic media and their participation in digital communication.
Keywords: Cultural identity; YouTube; Vlogs; Vietnamese diaspora; Media; Communication